(untitled) (Boletin Médico de Postgrado, 2020)
Recurrent respiratory papillomatosis (RRP) is the second most frequent cause of dysphonia during childhood; the most frequent causative agent is human papillomavirus serotypes 6 and 11. In order to describe the clinical and epidemiological characteristics of RRP In pediatric admitted to the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga, a cross-sectional descriptive study was conducted during the 2011-2016 period. The average age of diagnosis was 4.4 ± 2.41 years, with the highest prevalence in preschool children (70%) and with no sex predilection. 90% of patients were product of vaginal delivery and 30% reported asthma and low respiratory infection. The clinical features present were dysphonia (90%), dyspnea (70%) and stridor (60%); location of the lesions were anterior commissure (100%), vocal folds (80% right and 90% left) and vestibule (40%). 40% of patients reported HPV-6 and 10% HPV-11. Treatment was surgical in 100% of cases of which 50% required a second pruning and 30% three pruning; 10% needed a tracheotomy. This study provides information on the importance of early recognition of persistent dysphonia allowing to reduce diagnosis delay of RRP and facilitate timely management with lower rates of long-term recurrence.